MEMBACA ULANG RELASI SAINS DAN AGAMA DALAM PERSFEKTIF NALAR ILMU FALAK - Chotban, Sippah (ELFALAKY: Jurnal Ilmu Falak, 2020)
The discourse on the relationship between Science and Religion continues to be discussed by various groups. This dialogue increasingly finds space for its actuality, especially when the world is shocked by the outbreak of a disease called Covid 19. Its existence does not only present a variety of wild speculations at least about its origin, but also reopens classical discourse on the relation of Science and Religion; whether in line or even contradictory. As always, it always creates a split in views and attitudes towards it There are pros and cons. In such a context, it is interesting to restate the polemic of the relation between Science and Religion within the framework of the science of Falak reasoning. With it, the authentic face of the relation between Science and Religion will be identified again in an Islamic perspective.Keywords: Falak Science; Science and Religion Relations